Redistribution of interlocutors’ roles as a factor of topic recontextualization - Kovalchuk, Liudmyla V.; Ковальчук, Людмила Володимирівна (Харківський національний університет імені В.Н. Каразіна, 2016)
The given article deals with the study of peculiarities of topic recontextualization under conditions of redistribution of interlocutors’ roles. We singled out basic cases of redistribution of communicative partners’ roles, such as free-will transference of the communicative initiative by the speaker to the listener, self-willed seizure of the communicative initiative by the listener and modification of the communicative status of the side-recipient (from a passive observer to an active participant). Special attention is focused on the analysis of linguistic markers of topic recontextualization in discourse caused by redistribution of interlocutors’ roles. Стаття присвячена дослідженню особливостей реконтекстуалізації топіка в умовах перерозподілу ролей співрозмовників. Виокремлені основні випадки перерозподілу ролей комунікативних партнерів, такі як добровільна передача комунікативної ініціативи мовцем слухачеві, самовільне захоплення комунікативної ініціативи слухачем та модифікація комунікативного статусу стороннього реципієнта (від пасивного спостерігача до активного учасника). Особлива увага фокусується на аналізі лінгвістичних маркерів реконтексталізації топіка в дискурсі, спричиненої перерозподілом ролей співрозмовників.
Перерозподіл ролей співрозмовників як фактор реконтекстуалізації топіка
Keywords: context model; interlocutor; redistribution of roles; recontextualization; topic; контекстуальна модель; перерозподіл ролей; реконтекстуалізація; співрозмовник; топік